ANALISIS PENGARUH BETA TERHADAP RETURN SAHAM MENGGUNAKAN UNCONDITIONAL APPROACH DAN CONDITIONAL APPROACH (Studi Kasus pada Perusahaan yang Tergabung di Jakarta Islamic Index Periode Tahun 2013-2016) - Puji Astuti, Aisyah Intan; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2018)
The relationship between beta and return has always been a controversy invarious studies. Many studies proves that the Capital Asset Pricing Model (CAPM) model is able to describe the variation of returns caused by beta. But several studies deny that beta can not be used as a basis for estimating return. This study aims to analyze the relationship between beta and return as a validity test of Capital Asset Pricing Model (CAPM) theory using the Unconditional and Conditional approach.The population in this study are all companies listed on Indonesian Stock Exchage which are included on Jakarta Islamic Index in period 2013-2016 and took 8 companies as a research sample . The secondary data of this research is obtained from Yahoo Finance and official website of Bank Indonesia. The analytical method used in this research is simple linear regression model with SPSS 24 program.The result of this research explains that beta has a significant positive effect to stock returns using unconditional approach while another approach, conditional approach, explains that beta has a significant positive effect to stock returns during market risk premium positive (up market) and an insignificant positive effect during market risk premium negative (down market)